The hungry season - Greenwood, T. (Tammy) (Kensington, 2010)
"It's been five years since the Mason family vacationed at the lakeside cottage in northeastern Vermont, close to where prize-winning novelist Samuel Mason grew up. The summers that Sam, his wife, Mena, and their twins Franny and Finn spent at Lake Gormlaith were noisy, chaotic, and nearly perfect. But since Franny's death, the Masons have been flailing, one step away from falling apart. Lake Gormlaith is Sam's last, best hope of rescuing his son from a destructive path and salvaging what's left of his family. As Sam struggles with grief, writer's block, and a looming deadline, Mena tries to repair the marital bond she once thought was unbreakable. But even in this secluded place, the unexpected--in the form of an over-zealous fan, a surprising friendship, and a second chance--can change everything" -- from publisher's web site.